The Role of Orphanages In Empowering Abandoned Children Who Are Cared For at Orphanages - Tjempaka, Tjempaka; Christy , Stephanie (Dinasti Research, 2024)
Every child definitely wants genuine affection and attention from their parents and a place to live that can protect them, because they have the right to get all of that. However, not all children can feel what they want. Sometimes they are placed in orphanages for economic reasons or other reasons. This is a complex social problem that researchers want to address as research and the city chosen is the Aisyiyah Orphanage which is located in the Ngampilan area, Yogyakarta. The issues that will be raised are why the orphanage wants to accept babies/children to be entrusted to their parents and how does the orphanage empower the babies/children being cared for/entrusted so that when they reach adulthood they can be independent? The research methodology used is a qualitative approach which is then outlined in a descriptive method. Data collection was carried out by interviews. The results of the research show that to empower babies/children cared for in the Aisyiyah Sleman Orphanage, Yogyakarta is to provide education in general and provide skills that can support their future.